Border Ethics: Translation and Planetarity in Spivak - Ganguly, Avishek (Intermédialités / Intermediality)

(untitled) (Revue intermédialités, 2019)
This article revisits two influential essays by Gayatri Chakravorty Spivak, “The Politics of Translation” (1992) and “Imperatives to Re-Imagine the Planet” (1999), and aims to connect and foreground their shared preoccupation with the ethical as “experience of the impossible.” I argue that, crucially for our contemporary moment, these two essays also think borders—linguistic, disciplinary, political, geographic—but eschew the familiar “bordered/borderless binary”; instead, Spivak seeks to displace the border question altogether onto the scale of planetarity, beyond categories of local/global or national/international where the planet is understood to be in a “species of alterity,” an otherness that is not and cannot be derived from us, “the globe.”